2021
DOI: 10.1158/1078-0432.ccr-20-4746
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I/Ib Clinical Trial of Sabatolimab, an Anti–TIM-3 Antibody, Alone and in Combination with Spartalizumab, an Anti–PD-1 Antibody, in Advanced Solid Tumors

Abstract: Purpose: Sabatolimab (MBG453) and spartalizumab are mAbs that bind T-cell immunoglobulin domain and mucin domain-3 (TIM-3) and programmed death-1 (PD-1), respectively. This phase I/II study evaluated the safety and efficacy of sabatolimab, with or without spartalizumab, in patients with advanced solid tumors. Patients and Methods: Primary objectives of the phase I/Ib part were to characterize the safety and estimate recommend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(129 citation statements)
references
References 37 publications
4
125
0
Order By: Relevance
“…Importantly, a number of preclinical studies have shown that, compared with the use of anti-PD-1 antibody alone, the combined treatment of blocking Tim-3 and PD-1 can significantly improve the survival rate of mice (59,87). Moreover, several ongoing clinical trials have also evaluated the safety and efficacy of the combination therapy (88,89). Therefore, the combined blockade of Tim-3 and PD-1 pathway might be a promising strategy for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, a number of preclinical studies have shown that, compared with the use of anti-PD-1 antibody alone, the combined treatment of blocking Tim-3 and PD-1 can significantly improve the survival rate of mice (59,87). Moreover, several ongoing clinical trials have also evaluated the safety and efficacy of the combination therapy (88,89). Therefore, the combined blockade of Tim-3 and PD-1 pathway might be a promising strategy for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients receiving combination treatment had partial responses (6%; lasting 12-27 months) in colorectal cancer (n = 2), non-small cell lung cancer (NSCLC), malignant perianal melanoma, and SCLC. Of the five, two patients had elevated expression of immune markers in baseline biopsies; another three had >10% TIM-3-positive staining, including one patient with NSCLC who received prior PD-1 therapy (88). It suggested that sabatomimab combined with spartalizumab was well tolerated and showed preliminary signs of antitumor activity.…”
Section: Clinical Trials Of Targeting Both Pd-1 and Tim-3 In Human Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding combined checkpoint inhibitors, a phase I study found manageable safety and promising antitumor activity with the antilymphocyte activation gene (LAG-3) antibody plus pembrolizumab in MSS mCRC ( 54 ). Anti-TIM-3 antibody combined with anti-PD-1 antibody showed preliminary signs of antitumor activity in solid tumors ( 55 ).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…There are several anti-TIM-3 monoclonal antibodies in (pre)clinical development [ 62 ], such as (i) sabatolimab which is currently evaluated for the treatment of advanced solid tumors [ 63 ] and myelodysplastic syndromes [ 64 ], (ii) the fully human anti-TIM-3 antibody M6903 in preclinical development [ 65 ], (iii) LY3321367 currently tested in advanced solid tumors [ 66 ], and a few other antibodies [ 49 , 67 ] ( Table 1 ). Over the past two years, TIM-3 has emerged as an important immune-checkpoint molecule and recent data demonstrated that the receptor plays multiple roles, well beyond CD4 + /CD8 + T cells, notably as a key regulator of dendritic cell functions via the regulation of inflammasome activation [ 68 ].…”
Section: The Tim-3 Immune Checkpoint and Its Targeting With Antibodiesmentioning
confidence: 99%